Quality of Life and Mental Health Status of Arsenic-affected Patients in a Bangladeshi Population
Contamination of groundwater by inorganic arsenic is one of the major public-health problems in Bangladesh. This cross-sectional study was conducted (a) to evaluate the quality of life (QOL) and mental health status of arsenic-affected patients and (b) to identify the factors associated with the QOL. Of 1,456 individuals, 521 (35.78%) were selected as case and control participants, using a systematic random-sampling method. The selection criteria for cases (n=259) included presence of at least one of the following: melanosis, leucomelanosis on at least 10% of the body, or keratosis on the hands or feet. Control (nonpatient) participants (n=262) were selected from the same villages by matching age (